Agriculture and Industry in the Brazilian Midwest between the Decades of 1960 and 1980: Class Analysis - Herick Vazquez Soares (Historia y Sociedad, 2018)
The paper seeks to understand the macroeconomic context of the Brazilian Agroindustrial Complex’s constitution process and the incorporation of the Central-West region into the national economic space between 1965 and 1980 in order to analyze the regional class structure engendered by this process. This analysis is done through the bibliographical and documentary survey of sectoral, economic and regional public policies that led to the acceleration of the industrialization process in the country during the military governments. This is articulated with the analysis of data from the population, agricultural and industrial censuses of the 1965-1980 period. From this survey, the article makes a theoretical reflection on the framework of the Latin American Dependency Theory regarding the class structure originated from the incorporation of the Center-West region into the national economic space. The results of the study demonstrate that the incorporation of the Central West region into Brazilian capitalism took place by means of a joint action between State, landowners and agroindustrial capitals, and that it was a relevant step toward the change in Brazil’s position in the international division of labor and toward its differentiation regarding other peripheral countries. This incorporation, whose rhythm of expansion and development patterns were derived from the new agricultural technologies and from the domain of capitalist land ownership, generated a regional class pact whose discussion and reflection must take into account its similarity with the social tripod described by the Theory of Latin American Dependence, considering it typical of a dependent industrialization on an essentially agricultural region, yet indicating the industrial character of modern capitalist farming.